Avaliação de uma instituição na área da saúde com base no programa de acreditação hospitalar: um estudo de caso - Campos, Ana Claudia Burgermeister (2006)
Nowadays, the risk situations to the health that can cause damage, or lesion, are countless, being constituted risk situations, so much the environmental conditions, the products of direct and indirect consumption, as for the human interrelations. The lenders services entities to health, looking for the efficiency and effectiveness of their methods and practices, the dinamization and optimization of their resources, they seek the excellence of their activities, in benefit of the promotion of health of the population. For so much, was formulated a concept of Accreditation - that means to grant, to an organization, an evaluation certificate that expresses the conformity with a group of patterns, previously established, developed in its national format by ONA - National Organization of Accreditation. The present study objected to evaluate an institution in health area, in this case, the Santa Maria's Military Brigade Hospital (HBMSM), with base in Hospital's Accreditation Program. This institution has a military character, auxiliary force of the State of Rio Grande do Sul Government. To acilitate the understanding of the objective of this research, it was made a theoretical referential focusing the Quality in Services, Quality in Services in Health Area, Sanitary Surveillance and Hospital s Accreditation. The study has an exploratory nature, and it also presents characteristics of qualitative research, and descriptive too, with characteristics of classic inductive method of the case study. It was used an instrument containing all the eight sections, and their respective subsections, of National Organization Hospital's Accreditation Manual that evaluated from the Leadership and Administration to the practice of Teaching and Research, inside of the institution. Then, all conform and no-conform points were analyzed, helping the institution to reach its final objective. The results showed that in spite of HBM/SM to work well, and possess no one type of serious mistakes, it is necessary, to get the Accreditation Certificate, larger cares in the physical structure, of the hospital, and the continuation of the demanded legislations, the institution will guarantee full safety to the internal and external customers.